A Facial Synthesis and Antimicrobial Activity of Some Pyrazole Derivatives Carrying Indole - K. Narasimha Sarma; M. C. S. Subha; K. Chowdoji Rao (E-Journal of Chemistry)
The title compounds (7a-h) were prepared by esterification of indole-5-carboxylic acid (1) and subsequent treatment with hydrazine hydrate in methanol via the hydrazide (3). Finally hydrazide (3) condensed with different substituted aldol (6) in acetic acid / PTSA catalytic media produced (3,5-subsituted-4,5-dihydropyrazol-1-yl)(1H-indol-5-yl)methanone (7a-h) in good yields. All the newly synthesized compounds are by elemental analysis and spectral studies and evaluated for antimicrobial activities.